2010
DOI: 10.1007/s10853-010-5010-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnesium alloys reinforced with nanoparticles and carbon nanotubes: a review

Abstract: Magnesium alloys suffer from only moderate high-temperature strength and creep resistance. Aluminium-free magnesium alloys for sand casting or alloys containing aluminium with expensive additional alloying elements may be in use, but only microparticle or microfibre-reinforced magnesium alloys really exhibit satisfactory creep strengths at temperatures up to 250°C. Reinforcing magnesium alloys with ceramic nanoparticles could be a solution for preserving a low density while increasing the high-temperature perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(74 citation statements)
references
References 45 publications
5
69
0
Order By: Relevance
“…Various researchers have observed the simultaneous improvement in strength and ductility in Mg and its alloys through the addition of insoluble metallic elements like Ti, Mo and nano-sized ceramic particulates (Al 2 O 3 , Y 2 O 3 ). Similar results were also obtained by Eugene et al through the addition of nano-sized Cu particulates having limited solubility in Mg [14][15][16][17][18][19][20]. Recently, the high strength, high modulus, hard intermetallic phases (such as Al 3 Ti and TiB 2 , etc.)…”
Section: Introductionsupporting
confidence: 79%
“…Various researchers have observed the simultaneous improvement in strength and ductility in Mg and its alloys through the addition of insoluble metallic elements like Ti, Mo and nano-sized ceramic particulates (Al 2 O 3 , Y 2 O 3 ). Similar results were also obtained by Eugene et al through the addition of nano-sized Cu particulates having limited solubility in Mg [14][15][16][17][18][19][20]. Recently, the high strength, high modulus, hard intermetallic phases (such as Al 3 Ti and TiB 2 , etc.)…”
Section: Introductionsupporting
confidence: 79%
“…Although they did not observe any effect on grain size, the ductility slightly decreased, and tensile yield strength slightly increased. An overview of nanoparticle reinforced magnesium alloys is given in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among MMCs materials, micro-sized particulate MMCs attract more attention from both industries and academia than fibre reinforced MMCs, as the former category exhibits higher ductility and lower anisotropy [2]. With the development of materials science, it has been reported that MMCs reinforced with small volume fraction of nano-sized particles could produce even superior results in mechanical properties than those reinforced with micro-sized particles [3][4][5].…”
Section: Introductionmentioning
confidence: 99%